Protein-Ligand Interactions of the D-Galactose/D-Glucose-Binding Protein as a Potential Sensing Probe of Glucose Biosensors. Issue 5 (11th July 2012) - Stepanenko Stepanenko, Olga V. Olga V.; Stepanenko Stepanenko, Olesya V. Olesya V.; Fonin Fonin, Alexander V. Alexander V.; Verkhusha Verkhusha, Vladislav V. Vladislav V.; Kuznetsova Kuznetsova, Irina M. Irina M.; Turoverov Turoverov, Konstantin K. Konstantin K.
Abstract : In this paper we have studied peculiarities of protein-ligand interaction under different conditions. We have shown that guanidine hydrochloride (GdnHCI) unfolding-refolding of GGBP in the presence of glucose (Glc) is reversible, but the equilibrium curves of complex refolding-unfolding have been attained only after 10-day incubation of GGBP/Glc in the presence of GdnHCl. This effect has not been revealed at heat-induced GGBP/Glc denaturation. Slow equilibration between the native protein in GGBP/Glc complex and the unfolded state of protein in the GdnHCl presence is connected with increased viscosity of solution at moderate and high GdnHCl concentrations which interferes with diffusion of glucose molecules. Thus, the limiting step of the unfolding-refolding process of the complex GGBP/Glc is the disruption/tuning of the configuration fit between the protein in the native state and the ligand.